Airbnb amenities: Quantifying their contribution to the guest experience - Wondwesen Tafesse; Urwa Tariq (Annals of Tourism Research Empirical Insights)
Due to the expectation that Airbnb guests value home-benefit amenities, Airbnb hosts provide a wide range of amenities. These amenities can potentially enhance guests' experience by expanding the range of interactions they can have during their stay. However, empirical research systematically investigating the contribution of Airbnb amenities to the guest experience remains limited. To address this gap, the present study adopts an experiential perspective and organizes hundreds of individual amenities offered by Airbnb properties into 12 comprehensive and mutually exclusive categories. Using data from thousands of Airbnb listings, the study then quantifies the contributions of these categories to the guest experience. The findings reveal that certain categories including office, entertainment, ambiance, safety and accessibility amenities are significantly associated with the guest experience, while other categories including kitchen, living room, bedroom, bathroom, and outdoor amenities have no significant association with the guest experience. The findings contribute to the Airbnb literature by providing a systematic framework to categorize Airbnb amenities and offering empirical evidence of their contribution to the guest experience.